PREVALENCIA DE Giardia sp. EN Canis familiaris DE LOS DISTRITOS DE LA PROVINCIA CONSTITUCIONAL DEL CALLAO - Araujo T., William (2004)
The aim of this study was to determine the Giardia sp. prevalence in household dog populations on the six districts of the Provincia Constitucional del Callao. Fecal samples were collected from 385 apparently healthy dogs of various ages and processed by the spontaneous sedimentation technique. The results indicated the 9.4 ± 2% (36/385) of the canine population were positive to Giardia sp. cysts. Relationships between cysts detection and fecal samples characteristics, and origin, sex and age of dogs were analyzed by logistic regression. A significant statistical relationship was found between Giardia sp. detection and physical characteristics of fecal samples. Results show a moderate Giardia sp. infection in dogs which evidences a zoonotic risk that highlight the necessity of setting up educational programmes in order to prevent Giardia sp. Transmission, especially to infant population.